a. 4(x+5) = 10x + 3 a. 4x+20 =10x +3 a. 3-4x+20=10x a. 17-4x=10x a. 17=10x + 4x a. 17=14x a. 17 sur 14
moi g trouver 17/6
moi j'ai trouver 17/6
jai pas compris
jai...pas compris

Réponses

Meilleure réponse !
  • Utilisateur Brainly
2014-09-14T08:49:27+02:00
Ex 11.

4(x + 5) = 10x + 3
4x + 20 = 10x + 3
20 - 3 = 10x - 4x
17 = 6x
17/6 = x

3(x - 2) = 6(x + 4)
3x - 6 = 6x + 24
- 6 - 24 = 6x - 3x
- 30 = 3x
- 30/3 = x
- 10 = x

7x - (5x + 3) = 5(x - 3) + 2
7x - 5x - 3 = 5x - 15 + 2
2x - 3 = 5x - 13
- 3 - 13 = 5x - 2x
- 16 = 3x
- 16/3 = x

7(n + 2) - 3 = 25 - (3n + 4)
7n + 14 - 3 = 25 - 3n - 4
7n + 3n = 25 - 4 - 14 + 3
10n = 10
n = 10/10
n = 1

4y + 3(4y - 2) = 3(y + 1)
4y + 12y - 6 = 3y + 3
4y + 12y - 3y = 6 + 3
13y = 9
y = 9/13
2014-09-14T09:03:07+02:00
a)
4 (x + 5) = 10x + 3
4x + 20 = 10x + 3
4x - 10x = 3 - 20
- 6x = - 17
- x = - 17/6
x = 17/6

b)
3 (x - 2) = 6 (x + 4)
3x - 6 = 6x + 24
3x - 6x = 24 + 6
- 3x = 30
-x = 30/3
-x = 10

c)
7x - (5x + 3) = 5 (x - 3) + 2
7x - 5x - 3 = 5x - 15 + 2
7x - 5x - 5x = - 15 + 2 + 3
- 3x = - 12
3x = 12
x = 12/3
x = 4

d)
7 (n + 2) - 3 = 25 - (3n + 4)
7n + 14 - 3 = 25 - 3n - 4
7n + 3n = 25 - 4 - 14 + 3
10n = 10
n = 10/10
n = 1

e)
4y + 3 (4y - 2) = 3 (y + 1)
4y + 12y - 6 = 3y + 3
4y + 12y - 3y = 3 + 6
13y = 9
y = 9/13